Vector Bond Graph Method for the Dynamic Simulation of RRR-RRP Six Bar Press Linkage with Joint Clearance - Zhongshuang Wang; Jing Wei; Jiuzheng Yin (Jixie chuandong)
For the dynamic modeling and simulation of RRR-RRP six bar press linkage with joint clearance, the corresponding vector bond graph procedure is proposed. Under the condition of considering revolute joint clearance and compound revolute joint, the vector bond graph model of RRR-RRP six bar press linkage is established. By the corresponding method, the algebraic difficulty brought by differential causality of the mechanism vector bond graph model in automatic modeling and simulation is solved. Based on these, the computer automatic dynamic modeling and simulation of RRR-RRP six bar press linkage with joint clearance is realized, and the effect of joint clearance to the cutter acceleration, mechanism component angular acceleration, centroid acceleration of mechanism component and joint constraint force is analyzed. Finally, the reliability and validity of the procedure proposed are illustrated.